2019
DOI: 10.2139/ssrn.3404019
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transition, Poverty and Inequality: Panel Evidence from Vietnam

Abstract: This paper investigates energy transition, energy poverty and energy inequality in Vietnam employing a longitudinal dataset of a nationally representative household survey. We use the data on residential energy expenditure of more than 9,000 households over the period 2004 -2016. We find a transition from traditional energy to modern energy but this transition varies across regions, between ethnic and welfare groups and between rural and urban population. The poor and ethnic minority households still rely heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Her situation is similar to what Yeoh and her colleagues ( 2013) have noted about remittances, which are not always used appropriately for poverty escape in the home country, while migrants tend to suffer financial and work pressure for such an 'act of recognition' as 'dutiful' children (p. 453). The ineffectiveness of Anh Ngoc remittances also echoes the findings of some research (e.g., D. T. V. C. Nguyen, 2008; V. C. Nguyen & Mont, 2012) about the ineffectiveness of international remittances in poverty amelioration in Vietnam when beneficiaries tend to spend the money on domestic consumption.…”
Section: Migration For Economic Reasonssupporting
confidence: 74%
“…Her situation is similar to what Yeoh and her colleagues ( 2013) have noted about remittances, which are not always used appropriately for poverty escape in the home country, while migrants tend to suffer financial and work pressure for such an 'act of recognition' as 'dutiful' children (p. 453). The ineffectiveness of Anh Ngoc remittances also echoes the findings of some research (e.g., D. T. V. C. Nguyen, 2008; V. C. Nguyen & Mont, 2012) about the ineffectiveness of international remittances in poverty amelioration in Vietnam when beneficiaries tend to spend the money on domestic consumption.…”
Section: Migration For Economic Reasonssupporting
confidence: 74%
“…While the role of land size (quantity) in income and poverty for rural Vietnam has been extensively investigated (Van Hoang et al, 2019; Nguyen, 2011; Nguyen & Tran, 2018; Nguyen et al, 2021; Tran, Vu, Nguyen, et al, 2021; Viet Nguyen & Ngoc Tran, 2014), similar evidence for land quality is limited, possibly due to a lack of land quality data. Even where data is available, it is a considerable challenge for researchers to analyze the link between land quality and household economic well‐being because these variables are characterized by an endogenous relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large body of empirical research has confirmed the positive effect of agricultural land size on rural household livelihoods in Vietnam ( Van Hoang et al, 2019;Nguyen, 2011) and most developing countries (Barbier & Hochard, 2018;Besley & Burgess, 2000;DFID, 2002;Rutherford, 2012;Tran, 2014). However, land quality is frequently left out of accounts by researchers and is often proxied by error terms in econometric analyses (Berazneva et al, 2018), possibly due to the scarcity of data concerning land quality.…”
Section: Introductionmentioning
confidence: 99%